THE ROLE OF EMPLOYEE EMPOWERMENT, TEAMWORK, AND EMPLOYEE TRAINING ON ORGANIZATIONAL COMMITMENT - Restu Purba Riyadi; Zakky Fahma Auliya (IAIN Surakarta, 2021)
This study aims to determine the influence of employee empowerment, teamwork, and employee training on the organizational commitment of employees at the Banyumas Public Works Office. The population used is employees who work at the Department of Public Works of Banyumas Regency. The research method used was a quantitative method with a purposive sampling technique. The data analysis technique used was multiple linear regression. In this study. The data source used was primary data employing SPSS 23.0 software. Data collection methods in this study were questionnaires. The sample of this study was 80 respondents. The results of this study indicate that (1) employee empowerment has a significant influence on organizational commitment, (2) teamwork has a significant influence on organizational commitment, and (3) employee training has a significant influence on organizational commitment.